2016
DOI: 10.1016/j.visres.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and lustre: A model that accounts for eleven different forms of contrast discrimination in binocular vision

Abstract: Our goal here is a more complete understanding of how information about luminance contrast is encoded and used by the binocular visual system. In two-interval forced-choice experiments we assessed observers' ability to discriminate changes in contrast that could be an increase or decrease of contrast in one or both eyes, or an increase in one eye coupled with a decrease in the other (termed IncDec). The base or pedestal contrasts were either in-phase or out-of-phase in the two eyes. The opposed changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…However, we found that the results from both experiments were well described by a simpler model in which a single, linear binocular differencing channel is followed by a standard nonlinear transducer that is expansive for small signals but strongly compressive impression of luster, a cue that has been argued to enable detection of interocular differences (Formankiewicz & Mollon, 2009;Yoonessi & Kingdom, 2009;Malkoc & Kingdom, 2012;Jennings & Kingdom, 2016;Kingdom et al, 2018). Recent studies have suggested models for interocular difference detection based on luster (Georgeson et al, 2016;Jennings & Kingdom, 2016) and have furthermore demonstrated that interocular difference detection is an adaptable dimension of vision (Kingdom et al, 2018).…”
Section: $ #mentioning
confidence: 66%
See 1 more Smart Citation
“…However, we found that the results from both experiments were well described by a simpler model in which a single, linear binocular differencing channel is followed by a standard nonlinear transducer that is expansive for small signals but strongly compressive impression of luster, a cue that has been argued to enable detection of interocular differences (Formankiewicz & Mollon, 2009;Yoonessi & Kingdom, 2009;Malkoc & Kingdom, 2012;Jennings & Kingdom, 2016;Kingdom et al, 2018). Recent studies have suggested models for interocular difference detection based on luster (Georgeson et al, 2016;Jennings & Kingdom, 2016) and have furthermore demonstrated that interocular difference detection is an adaptable dimension of vision (Kingdom et al, 2018).…”
Section: $ #mentioning
confidence: 66%
“…This leaves open the question why a horizontally oriented Bþ channel is not involved. Recently, Georgeson et al (2016) put forward a model of binocular combination to account for the appearance of dichoptic mixtures of luminance contrasts and discrimination-threshold measures obtained in dichoptic masking experiments. They suggested that three channels were involved, two monocular (call these L and R) alongside the binocular summing Bþ channel.…”
Section: The Bà Channel and Efficient Codingmentioning
confidence: 99%
“…It therefore appears that humans have conscious access to information from their binocular visual system besides a mandatory binocular fusion of the two eyes' inputs. This information could include stereo depth from occlusion (McLoughlin and Grossberg, 1998), a binocular differencing channel (Li and Atick, 1994;May et al, 2012), or a 'lustre channel' that codes differences in luminance polarity across the eyes (Georgeson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…6), but in the first-order model ) the monocular channels are not influenced by the other eye, and always have a weight of 1.0. The idea of computing the max over monocular and binocular channel responses has also been successfully applied to explain dichoptic (first-order) contrast discrimination and contrast matching (Georgeson, Wallis, Meese, & Baker, 2016).…”
Section: A Predictionmentioning
confidence: 99%